2009
DOI: 10.1590/s0104-56872009000100007
|View full text |Cite
|
Sign up to set email alerts
|

Relações entre idade, porcentagem de consoantes corretas e velocidade de fala

Abstract: Speech performance, measured by the PCC, and speech rate increased according to age, resulting in significant differences between the three age groups. The increase of the PCC indexes and of speech rate were directly proportional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
1
5
0
1
Order By: Relevance
“…Furthermore, the results that were found in this present study concerning the speech rate, agree with the results obtained in a study 19 in which the authors concluded that the oral motor control, analyzed by the speech rate and measured by the PCC, varies according to the performance of speech, meaning that the lower the percentage of correct consonants, slower was the speech of the children analyzed.…”
Section: Speech Rate: Word Flow and Syllables Per Minutesupporting
confidence: 92%
“…Furthermore, the results that were found in this present study concerning the speech rate, agree with the results obtained in a study 19 in which the authors concluded that the oral motor control, analyzed by the speech rate and measured by the PCC, varies according to the performance of speech, meaning that the lower the percentage of correct consonants, slower was the speech of the children analyzed.…”
Section: Speech Rate: Word Flow and Syllables Per Minutesupporting
confidence: 92%
“…A study (24) applied such measure in the Brazilian Portuguese with the intention of verifying speech fluency and suggested a standardization that started to be used in several other studies (16,(25)(26)(27) . Later, such measure was also researched to complement the diagnostic of children with phonologic disorder (18) as well as to verify speech speed standards at the different speech language therapy alterations (17,26,27) . The results of the mentioned studies demonstrated that the SRPM measure was effective to identify differences and characteristics in different populations.…”
Section: Discussionmentioning
confidence: 99%
“…Lisp frequencies of 60% and 23.33% were observed during speech production in the UCLP and CP groups, respectively, with a significantly higher alteration frequency in the group with a cleft lip and palate. This result can be explained by the incorrect positioning of the tongue, which affects articulatory points and is occasionally found as a result of the dento-occlusal balance condition, structural alteration, and reduced intraoral cavity, even after surgical repair (1,(5)(6)(7)(8)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(23)(24)(25) .…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies, evaluated children without cleft lip and palate who had a speech disorder (10)(11)(12)(13)(14)(15)(16) . These studies demonstrated that children with a speech disorder produced most of the emissions at a slower rate (15,16) , with a significant positive correlation between age, percentage of correct consonants, and speed of speech (17) . Further, an increase in the speed of syllable emission was observed with increased age (11) .…”
Section: Introductionmentioning
confidence: 88%